ERYTHEMA NODOSUM POST-INFECTION OF THE UPPER AIRWAY - APROPOS OF TWO CASES - Filho, Fred Bernardes; Quaresma, Maria Victória; Vendramini, Dâmia Leal; Bonkevitc, Fernanda; Damiani, Leandro; Alves, Andreia Oliveira; Nery, José Augusto da Costa (Journal of the Portuguese Society of Dermatology and Venereology, 2014)
Erythema nodosum is a panniculitis characterized by the appearance of erythematous and painful subcutaneous nodules, usually accompanied by prodrome, which has a benign course, with a tendency for rapid spontaneous healing. Being able to accompany or precede various diseases makes it an important clinical and therapeutic challenge. The authors present two cases of erythema nodosum lesions whose appearance was preceded by infection of the upper airway and recovered uneventfully.